(untitled) (Global Journal of Human-Social Science, 2011)
Housing problems in terms of their quality is a serious concern in ogbomoso Majority of the houses has one form of defect The study examined the socio-economic characteristics of residents types of houses facilities and condition of buildings A total of 204 questionnaires were administered using systematic random sampling techniques Data were further analyzed with the aid of simple descriptive analytical technique The hypothesis was tested using ANOVA The study showed inadequate provision of facilities such as pipe borne water erratic power supply poor solid waste management and presence of substandard houses in the study area However there is urgent need for enforcement of planning regulations to improve the housing quality and facilities in the study area